Correlation and Categories of Meat Tenderness Based on Equipment and Panelist Test - Suryati, T; Arief, II; Polii, BN (ANIMAL PRODUCTION, 2008)
The objective of this study was to determine the correlation between Warner-Bratzler shear force (WBSF) and cooking loss with sensory local trained panelists rating on beef tenderness, also to determine WBSF range at each tenderness categories (extremely tender, tender, rather tender, rather tough, tough, and extremely tough). Meat from knuckles of Australian Beef Cross (ABX) steer were broiled until internal temperature 70, 80 and 90oC to get some WBSF values. Cooking loss was counted as percentages of meat weight losses during cooking. Each WBSF values and cooking loss data were correlated with panelists test scores used linier regression equation. Then, based on that linier regression were estimated WBSF range at each tenderness level. The result indicated that WBSF was positive correlated with panelists test that was indicated with determination coefficient 0.7668 (r2 = 0.7668). Cooking loss was strongly positive correlated with panelists rating tenderness (r2 = 0.8114).Â  The result of meat tenderness range categories: extremely tender 0â3.30 kg/cm2, tender >3.30â5.00 kg/cm2, rather tender >5.00â6.71 kg/cm2, rather tough >6.71â8.42 kg/cm2, tough >8.42-10.12 kg/cm2, extremely tough >10.12 kg/cm2. (Animal Production 10(3): 188-193 (2008)Â Key Words: Meat tenderness, tenderness categories, panelist test, Warner-Bratzler shear, force, cooking loss